Implementation of the MBKM Curriculum of the FKIP UMN Al Washliyah in the PBSI Study Program of Delitua Kuta Manuscript Philology Based on the Project-Based Learning Method - Hasibuan, Abdullah; Nirmawan, Nirmawan; Silalahi, Cita Aini (West Science Interdisciplinary Studies, 2025)
The urgency of the Independent Curriculum is highly relevant to current learning, particularly in the selection of learning methods (Yamin & Syahrir, 2020) [1]. The Independent Curriculum effectively improves 21st-century skills such as critical thinking, communication, and creativity to produce competitive graduates (Jufriadi et al., 2022) [2]. Data collection techniques for this study included observation, document analysis, and interviews. The results of this study indicate that the implementation stage of project-based learning includes three stages: the initial stage, the development stage, and the conclusion stage, specifically in the study of the philology of the Kuta Delitua manuscript. The main difference between the project-based implementation stages lies in the initial stage applied. The purpose of the Independent Curriculum Implementation is to be a learning resource to mature teachers' pedagogical, social, and personality competencies (Daga, 2021). The Independent Curriculum is expected to overcome the learning crisis. The implementation of the Independent Curriculum through learning must be fun and innovative so that it fosters positive attitudes in children in learning (Suhartono, 2021) [3]. There are three concepts focused on independent learning, namely, commitment to learning goals according to their needs, interests, and aspirations (Rosdiana, 2022). Therefore, curriculum changes must be carried out systematically and holistically that can have an impact on the entire learning committee, the Philology of the Kuta Delitua Manuscript which is the forerunner of the village's origins. The targeted output in this study is as an evaluation and input to lecturers and students, especially in the Philology Study of the Kuta Old Deli Manuscript based on the Project Based Learning method in the implementation of the independent curriculum of the independent campus at UMN Al-Washliyah.